Implementasi Digitalisasi Administrasi Keuangan pada Dinas Perhubungan Kota Bandung: Studi Praktik Kerja Lapangan - Octavian, Fadilla Nur; Yudhanegara, Firman (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The digitalization of financial administration is one of the government’s strategies to improve the effectiveness, efficiency, transparency, and accountability of regional financial management. The Bandung City Transportation Agency has implemented digital-based administrative systems to support integrated financial document management and administrative processes. This study aims to describe the implementation of digital financial administration at the Bandung City Transportation Agency through an Internship Program. The research employed a descriptive method with a qualitative approach. Data were collected through direct observation during the internship, documentation, and relevant literature review. The findings indicate that the implementation of a digital financial administration system has accelerated administrative processes, facilitated financial document management, improved the accuracy of financial recordkeeping, and strengthened coordination among departments. However, several challenges remain, including limited user understanding of the system and the need to enhance human resource competencies in utilizing information technology. Therefore, continuous training and optimization of digital system utilization are essential to support more effective, efficient, transparent, and accountable financial administration.